Praktik Literasi Keuangan dalam Pengelolaan Usaha: Studi pada Pemilik UMKM di Kabupaten Bantul, Yogyakarta - Ruscitasari, Zulfatun; Nurcahyanti, Febriani Wahyusari; Wibisono, Dimas (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
The aim of this study is to examine the impact of financial literary on financial planning and control in Indonesian Micro, Small and Medium Enterprises (MSMEs). The mediating effect of proactive employees was also investigated. Data were collected from survey that involved 157 owners of MSMEs in Bantul District, Yogyakarta, Indonesia. Using Partial Least Square (PLS), this study found that financial behavior affects proactive employees, and proactive employees has significant impact on financial planning and control among the studied MSMEs. Besides, the results of this study confirm the mediating role of proactive employee on the relationship between financial literacy and financial planning and control level in MSMEs.